Suggested Approach to Solve Nonlinear Ordinary Differential Equations - A. Hussein, Noor; Obaid, Firas Jawad (JOURNAL OF ADVANCES IN MATHEMATICS, 2023)
In this research a suggested method has been proposed to solve the non-linear ordinary differential equations, This method is somewhat similar to the Adomain decomposition method of solving equations but it is quite different in the using steps to find the non-linear boundaries , in the suggested method does not use an unknown parameter to calculate non-linear boundaries as well as the steps used to calculate non-linear boundaries are very simple and do not need many and complex steps. we can be called this approach by Fatima style to solve nonlinear ODE.